Work-Family Conflict and Unethical Pro-family Behavior: The Mediating Effect of Threat Appraisal and the Moderating Effect of Family Collectivism Orientation - Li, Mozhi; Zhang, Lanxia; Zhang, Zhuo; Hai, Xin (Frontiers in Psychology, 2022)
Unethical pro-family behavior (UPFB) is prevalent in organizations and has adverse effects on organizations, but very few studies have examined the factors that lead to UPFB. We use a cognitive appraisal theoretical framework to argue that employees’ unethical pro-family (UPFB) behavior results from work and family conflicts (WFC/FWC) are mediated by threat appraisal and moderated family collectivism orientation. Based on the questionnaire data of 496 full-time employees from two-time points, we found that WFC/FWC was positively correlated with UPFB where threat appraisal played a mediating role in this relationship; Family collectivism orientation strengthens the threat appraisal-UPFB relationship and the mediation relationship between WFC/FWC and UPFB via threat appraisal. These findings offer an understanding of the theoretical and practical implications which could help organizations reduce UPFB. Finally, we discuss possible directions for future research.